Rab11a-positive compartments in proximal tubule cells sort fluid-phase and membrane cargo - Mattila, Polly E. (American Physiological Society, 2013)
The proximal tubule (PT) reabsorbs the majority of sodium, bicarbonate, and chloride ions, phosphate, glucose, water, and plasma proteins from the glomerular filtrate. Despite the critical importance of endocytosis for PT cell (PTC) function, the organization of the endocytic pathway in these cells remains poorly understood. We have used immunofluorescence and live-cell imaging to dissect the itinerary of apically internalized fluid and membrane cargo in polarized primary cultures of PTCs isolated from mouse kidney cortex. Cells from the S1 segment could be distinguished from those from more distal PT segments by their robust uptake of albumin and comparatively low expression of γ-glutamyltranspeptidase. Rab11a in these cells is localized to variously sized spherical compartments that resemble the apical vacuoles observed by electron microscopy analysis of PTCs in vivo. These Rab11a-positive structures are highly dynamic and receive membrane and fluid-phase cargo. In contrast, fluid-phase cargoes are largely excluded from Rab11a-positive compartments in immortalized kidney cell lines. The unusual morphology and sorting capacity of Rab11a compartments in primary PTCs may reflect a unique specialization of these cells to accommodate the functional demands of handling a high endocytic load.